2020
DOI: 10.1038/s41598-020-77760-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in cell size and corresponding cell fate after optic nerve injury

Abstract: Identifying disease-specific patterns of retinal cell loss in pathological conditions has been highlighted by the emergence of techniques such as Detection of Apoptotic Retinal Cells and Adaptive Optics confocal Scanning Laser Ophthalmoscopy which have enabled single-cell visualisation in vivo. Cell size has previously been used to stratify Retinal Ganglion Cell (RGC) populations in histological samples of optic neuropathies, and early work in this field suggested that larger RGCs are more susceptible to early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
(76 reference statements)
2
10
0
Order By: Relevance
“…Urcola et al described this as "hypertrophy". Because RGC somal and nuclear areas have previously been shown to be positively correlated (Davis et al, 2020;Janssen et al, 2013), it seems likely that the "hypertrophy" observed by Urcola et al, and "spreading" described here, are the same phenomenon. Davis et al (Davis et al, 2020) observed RGC nuclear enlargement in the early stages following partial optic nerve transection and hypothesized that it might involve metabolic responses of the injured RGCs.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Urcola et al described this as "hypertrophy". Because RGC somal and nuclear areas have previously been shown to be positively correlated (Davis et al, 2020;Janssen et al, 2013), it seems likely that the "hypertrophy" observed by Urcola et al, and "spreading" described here, are the same phenomenon. Davis et al (Davis et al, 2020) observed RGC nuclear enlargement in the early stages following partial optic nerve transection and hypothesized that it might involve metabolic responses of the injured RGCs.…”
Section: Discussionsupporting
confidence: 68%
“…Because RGC somal and nuclear areas have previously been shown to be positively correlated (Davis et al, 2020;Janssen et al, 2013), it seems likely that the "hypertrophy" observed by Urcola et al, and "spreading" described here, are the same phenomenon. Davis et al (Davis et al, 2020) observed RGC nuclear enlargement in the early stages following partial optic nerve transection and hypothesized that it might involve metabolic responses of the injured RGCs. Because we have observed spreading in not only glaucomatous RGCs, but also in non-RGCs of mice with glaucoma and in RGCs of healthy WT mice, we propose a more passive response-though future studies to study this phenomenon are needed.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations